A review of the genus Dudaia Hedicke, 1923 (Diptera, Sphaeroceridae) - Papp, László; Norrbom, Allen L. (Zootaxa, 2015)
Species of the Afrotropical genus Dudaia Hedicke, 1923 of the subfamily Copromyzinae are revised. The status of Afroborborus Curran, 1931 as a junior synonym of Dudaia is corroborated. Twelve species have been described hitherto, two of them are proposed here to be junior synonyms: Copromyza (Dudaia) simulatilis Richards, 1980, and the name it replaced, Borborus (Dudaia) similis Vanschuytbroeck, 1948, are junior synonyms of Copromyza (Gymnometopina) jeanneli Richards, 1938; and Borborus (Dudaia) uelensis Vanschuytbroeck, 1959 is a junior synonym of Dudaia straeleni (Vanschuytbroeck, 1948). Ten species new to science are described: Dudaia abdita sp. nov. (Kenya), Dudaia aethiopica sp. nov. (Ethiopia), Dudaia albimana sp. nov. (Madagascar), Dudaia brevis sp. nov. (Madagascar), Dudaia communis sp. nov. (Democratic Republic of Congo, Republic of Congo, Ghana, Nigeria, and Tanzania), Dudaia malagasiensis sp. nov. (Madagascar), Dudaia microtuberculata sp. nov. (South Africa), Dudaia pseudohumeralis sp. nov. (Democratic Republic of Congo), Dudaia spangleri sp. nov. (Kenya), and Dudaia steineri sp. nov. (Madagascar).